Legal Aspects of Inheritance in the Batak community in Parapat - Imman Yusuf Sitinjak; Humala Sitinjak (Budapest International Research and Critics University, 2022)
This study aims to determine how the implementation of in heritance that occurs and the problems that often occur with inheritance in the Batak community in Parapat. Inheritance is not a problem if it is carried out in accordance with the provisions of the division of inheritance, and the division of inheritance is carried out by mutual agreement. However, currently there are many problems that occur when inheritance is not carried out evenly, and it is not uncommon for inheritance to become a dispute for each heir. This study discusses the implementation of community inheritance in Parapat as well as the problems that often occur in the implementation of inheritance and the problem of transferring inheritance rights to the Batak community in Parapat. In the Parapat community, the dominant ethnicity is the Batak, most of them carry out inheritance by dividing the inheritance of customary law. The implementation of the division of inheritance is by focusing on boys as heirs, while for girls it is only limited to